To Evaluate In Vitro Antioxidant Property Of Sugarcane ( Saccharum Officinarum L ) Peel - S. ELAKKIYA,; R. PALLAVI,; SAI SIVA RAM TENNETY,; P.SUGANYADEVI, (International Journal of Pharma and Bio Sciences, 2012)
The Sugarcane (Saccharum officinarum L.) is a widely distributed plant. It is an important source for sugar and raw material for alcohol production. In the present study, sugarcane peel was used as a source for anthocyanin extraction. Anthocyanins are natural pigments, which are responsible for red, purple and blue colours in parts of the plant. It belongs to a major flavonoid class which has strong antioxidant activity. In the present scenario, there is a rising demand for natural sources of food colorants with nutraceutical benefits. So the present research focus on the antioxidant activity of anthocyanin extracted from sugarcane peel. Antioxidant assays were analysed by DPPH, hydroxy radical scavenging, reducing power, metal chelating, hydrogen peroxide, deoxyribose degradation (site specific & non -site specific) and ABTS assays. From the results, it was confirmed that anthocyanin extracted from sugarcane peel has potent antioxidant properties. Finally, ensure that the anthocyanin extracted from sugarcane peel replace many synthetic food colorants and chemical antioxidants.